The 4T Approach for Smoking Cessation Compliance for Pulmonary Tuberculosis Patients in Persahabatan Referral Hospital - Septauli, Kolanda Maria; Susanto, Agus Dwi; Agustin, Heidy; Ginting, Tribowo Tuahta; Taufik, Feni Fitriani (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Smoking increases the risk of tuberculosis infection and affects its treatment success rate and mortality. Most TB patients who smoke quit at the initial diagnosis, but may continue to smoke if the clinical symptoms improve. Studies show that the 4T approach (Tanya, Telaah, Tolong nasehati, and Tindak lanjut) helps smokers quit. The 4T approach was applied in Indonesia as a smoking cessation program for TB patients.Methods: We conducted a randomized controlled trial on 43 male TB patients who smoke. The trial group received a 4T approach consisting of education, counseling, and motivation to quit smoking for three months. The control group received a self-help leaflet. Smoking status, Fagerström nicotine dependence scale, exhaled carbon monoxide level, and peak expiratory flow rate were collected. We observed the subjects at months 1, 2, and 3 after quitting smoking and reported on the Motivation and Minnesota Withdrawal Scale.Results: Smoking cessation levels during months I, II, and III (Continuous Abstinence Rate I, II, and III) were higher in the trial group than in the control group. The trial group had a higher percentage of smoking cessation than the control group: until 4 weeks (66.7% vs. 54.5%), until 8 weeks (57.1% vs. 45.5%), and until 12 weeks (52.4% vs. 45.5%). The control group had higher numbers of smoking relapses (18.2% vs. 14.3%) and still smokers (18.2% vs. 9.5%) after the study. Withdrawal symptoms included an increase in appetite (44.1%), cigarette cravings (6.9%), agitation (2.3%), insomnia (2.3%), and irritability (2.3%). There were no significant differences in the withdrawal scale between groups (P=0.788), but the trial group showed better motivation to stop smoking during CAR II (P=0.043).Conclusion: The 4T approach is effective in maintaining abstinence from smoking among lung tuberculosis patients until months 1, 2, and 3 after quitting. Smoking cessation programs during tuberculosis treatment can help patients quit smoking and reduce relapse.